2013
DOI: 10.4103/0259-1162.114012
|View full text |Cite
|
Sign up to set email alerts
|

To assess the efficacy of i-gel for ventilation, blind tracheal intubation and nasogastric tube insertion

Abstract: Background:The i-gel is a novel supraglottic airway device with a soft and non-inflatable cuff. In our study we attempted to evaluate the performance of i-gel as a ventilatory device, as a conduit to blind tracheal intubation using conventional polyvinyl chloride tracheal tube and gastric tube insertion through it.Materials and Methods:A total of 180 patients of American Society of Anesthesiologist (ASA) physical status I/II undergoing elective surgery under general anesthesia were included in this study. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
3
4
0
Order By: Relevance
“…The OLP of 32.1 cmH 2 O for the i‐gel and 32.8 cmH 2 O for the AuraGain, respectively, was higher than found in other studies with regular airway and lean patients. In those studies, an OLP of 25 cmH 2 O was reached . Similar OLP's as in our study were found by Keller in the ProSeal™ laryngeal mask in obese patients and for the AuraGain™ in a study by Lopez et al in patients undergoing gynecologic surgery, as in a study by Moser et al No data on obese patients exist for the AuraGain™.…”
Section: Discussionsupporting
confidence: 91%
“…The OLP of 32.1 cmH 2 O for the i‐gel and 32.8 cmH 2 O for the AuraGain, respectively, was higher than found in other studies with regular airway and lean patients. In those studies, an OLP of 25 cmH 2 O was reached . Similar OLP's as in our study were found by Keller in the ProSeal™ laryngeal mask in obese patients and for the AuraGain™ in a study by Lopez et al in patients undergoing gynecologic surgery, as in a study by Moser et al No data on obese patients exist for the AuraGain™.…”
Section: Discussionsupporting
confidence: 91%
“…The overall success ratewas 58.3% with I-GEL group compared to 90% with ILMS group [15] . Study by Bhandari, et al, found 95% success rate in first attempt in I-GEL group [16] .…”
Section: Discussionmentioning
confidence: 96%
“…Study by Latha Naik et al, stated that the time required for insertion of I-GEL was comparable with ILMA (p=0.860) [15] . Study by Bhandari, et al, found mean insertion time was 20.91 seconds [16] . M. Kleine Bruggeney et al, demonstrated that successful i-gel insertion time was 23 (±15) seconds [17] .…”
Section: Discussionmentioning
confidence: 98%
“…Studies and case reports demonstrated that an i-gel may be considered as an intubation conduit in the supine position. 3,[8][9][10][11][12] Manikin studies investigating the success rate of using an i-gel as an intubation conduit found conflicting results. 13,14 Our study demonstrates that in the prone position one should not rely on an i-gel as an intubation conduit.…”
Section: Discussionmentioning
confidence: 99%